2015
DOI: 10.1007/s00395-015-0525-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of adenosine A2A receptor activation diminishes beat-to-beat alternation in human atrial myocytes

Abstract: Atrial fibrillation (AF) has been associated with increased spontaneous calcium release from the sarcoplasmic reticulum and linked to increased adenosine A2A receptor (A2AR) expression and activation. Here we tested whether this may favor atrial arrhythmogenesis by promoting beat-to-beat alternation and irregularity. Patch-clamp and confocal calcium imaging was used to measure the beat-to-beat response of the calcium current and transient in human atrial myocytes. Responses were classified as uniform, alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Our results suggest that similar mechanisms may be at play in human AF as well, since increased propensity to CDA driven by RyR2 dysfunction led to increased arrhythmia vulnerability, complexity, and persistence in our model. Recent evidence for this comes from experiments in human atrial myocytes of control and AF patients, which identified a link between adenosine signaling, alternans, and calcium handling instability, potentially mediated by PKA regulation of RyR235. However, the mechanisms of RyR2 dysregulation in AF are extremely complex36 and controversial37.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that similar mechanisms may be at play in human AF as well, since increased propensity to CDA driven by RyR2 dysfunction led to increased arrhythmia vulnerability, complexity, and persistence in our model. Recent evidence for this comes from experiments in human atrial myocytes of control and AF patients, which identified a link between adenosine signaling, alternans, and calcium handling instability, potentially mediated by PKA regulation of RyR235. However, the mechanisms of RyR2 dysregulation in AF are extremely complex36 and controversial37.…”
Section: Discussionmentioning
confidence: 99%
“…264, 265 Atrial cardiomyocytes from patients with cAF are also more prone to Ca 2+ -alternans, an effect which appears to involve an increased activation of adenosine A 2A receptors with subsequent enhancement of RyR2-mediated SR Ca 2+ leak. 266 Overall, computer modeling clearly suggests that elevated Ca 2+ -driven APD alternans leads to increased arrhythmia vulnerability, complexity, and persistence due to increased heterogeneity of repolarization in atria. 267 …”
Section: Calcium-dependent Acquired Arrhythmiasmentioning
confidence: 99%
“…Prevention of A 2A receptor activation may be a novel way to maintain uniform beat-to-beat responses at higher beating frequencies in patients with AF. 132 Adenosineguided pulmonary vein isolation has been recommended, after a randomized clinical trial, for the treatment of paroxysmal AF, 133 but this has been questioned in a more recent clinical trial. 134 The clinical significance of ATP-induced AF has been investigated.…”
Section: Heart Diseasesmentioning
confidence: 99%